Improving the Quality of Trade Services in the Context of Innovative Development of the Country's Economy (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
This article discusses the role and importance of trading services, the quality of trading services and the culture of trading. The analysis of indicators of the quality of trading services of supermarket in Samarkand was carried out and recommendations were made to improve the trading services.